Pengaruh Current Ratio, Debt to Equity Ratio, dan Return On Assets terhadap Harga Saham Pada Perusahaan Sektor Property and Real Estate yang Terdaftar di BEI Periode 2014-2018 - Januardi Manullang; Pratama, Tri Ayu Dinanti; Rasinta Ginting; Lanissa Nuriza; Muhammad Fahmi (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
This study analyzes the effect of current ratio, debt to equity ratio and return on assets on stock prices. Which aims as material for investor consideration in determining the effect of the ratio on stock prices to help me choose which sector is most proper for investment. The data used in this study is the purposive sampling method which comprises twenty-seven property and real estate companies listed on the Indonesia stock exchange. The method used is multiple linear regression and the results of the study show that the current ratio has no effect and is not significant on stock prices, debt to equity ratio has a negative and significant effect on stock prices, return on assets has a positive effect on stock prices.